A Proposed Design of Knowledge Based Performance Management System For Airport Company - Dimas Haribowo; Akbar Adhi Utama (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
The aviation industry has an important role in connecting different regions of the world. Along with the economic recovery after the COVID-19 pandemic, improving airport performance is important to pay attention to. This research aims to design a knowledge-based performance management system that is suitable for airport companies. This research aims to identify critical factors that affect the performance of airport companies, identify organizations with critical functions, and design an integrated performance management system (IPMS) based on predetermined variables. This study uses a combination of theoretical analysis methods and model validation using data from airport companies in Indonesia. Data collection was carried out through questionnaire surveys and interviews. The Analytical Hierarchy Process (AHP) is used to select the appropriate variables by determining their level of significance. This study identifies 9 critical factors that must be considered in designing a performance management system for airport companies. These factors include business perspectives, internal processes, and resource capabilities. Furthermore, this study designs an integrated performance management system (IPMS) by determining Key Performance Indicators (KPIs), Cascade KPIs, targets, weights, and organizational functions involved. This research results in a knowledge-based performance management system design that can be applied to airport companies. This system is expected to help airport companies in improving their performance and achieving organizational goals.